Comparison of the Implementation of Good Faith in Indonesia, China, and Japan: Building Legal Harmonization - Miarsa, Fajar Rachmad Dwi; Zamroni, M.; Yoshida, Kunihiko (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The principle of good faith in contract law serves as a guiding principle for fairness, predictability, and trust in legal transactions. This principle, while universally recognized, finds varying interpretations and applications across different legal systems, reflecting the influence of their unique legal traditions, historical contexts, and legal cultures.Purposes of the Research: The principle of good faith in contract law serves as a guiding principle for fairness, predictability, and trust in legal transactions. This principle, while universally recognized, finds varying interpretations and applications across different legal systems, reflecting the influence of their unique legal traditions, historical contexts, and legal cultures.Methods of the Research: The research utilizes a multifaceted comparative legal research methodology. It combines doctrinal analysis of relevant legal provisions and case studies to illuminate the practical application of good faith in contract law. This approach goes beyond a mere textual analysis of legal provisions, providing a nuanced understanding of how good faith operates in practice within each jurisdiction.Results of the Research: The analysis reveals significant variations in the application of the good faith principle across jurisdictions, reflecting the influence of different legal traditions, historical contexts, and legal cultures. The research will highlight specific examples of how good faith is interpreted and applied in each jurisdiction, highlighting its impact on contract formation, performance, and termination.